Iryna Ivakhnenko. Archaeological activity of Vasyl’ Danylevych : Iryna Ivakhnenko. Archaeological activity of Vasyl’ Danylevych - Ivakhnenko, Iryna (Young Scholars Grinchenko – Seton International Journal, 2022)
Iryna Ivakhnenko. Archaeological activity of Vasyl’ Danylevych